Family-Owned SMEs, Internationalisation and Networks. The case study of the French family SME: "A La Prune Lorraine". - Loisy, Anne M. E. (2013)
Purpose: This exploratory research ambitionned to provide a better understanding of international network activities among family-owned SMEs. Precisely, its aim was to examine how networks effect the internationalisation activities of family SMEs. Three research questions were designed in order to fulfill a gap in the business literature: RO1: To explore the way in which family owned businesses manage their networks in their international activities. RO2: To examine how being a family-owned business is perceived by network members in their international development. RO3: To investigate the role that family members play in consolidating and developing international networks. Methodology: The researcher adopted a single case study method, using the French family business ‘A La Prune Lorraine’ (ALPL) as the unit of analysis. Eleven in-depth, semi-structured interviews were the primary data collection method. ALPL’s managers directly linked with international activities and family members were the first group of interviewees. Thereafter, business partners selected to represent ALPL’s international networks were interviewed. Findings: This study provides several contributions to the network theory of internationalisation in the context of family SMEs. Particularly, it was found that family SMEs do not rely on formal networks to develop their international network. French export-promotion agencies fail to fulfill their needs and international forums turn out to be more challenging than previously thought. Even though they allow firms to access actors from around the globe, family SMEs find it difficult to form new ties in such events. Family SMEs tend to commit fully into their business relationships abroad. They endeavour to set up an environment based on trust, long-term commitment and reciprocity, elements characteristics of strong ties. Interestingly, the family entrepreneur is said to play a great role in such enterprise. Furthermore, they tend to be affinities between family SMEs across borders. It was found that family SMEs appreciate their business relationships with foreign counterparts as they share similar culture and similar ways of working. Family SMEs can be good networks to develop, as long as the entrepreneur embodies the family culture. Finally, family members were found to be a great asset in international network building and consolidation. Their studies, experiences abroad and travels have shaped their global orientation and provided them with numerous international informal ties. Consequently, family members are bridging ties through which family SMEs can quickly become insiders into new markets. Research limitations: The single case strategy employed restricts the generalisability of the findings.